The Effects of LTAD-Based Programming on Fundamental Skills and Physical Abilities of Basketball Players Aged 11-12 Years - Taufiq Hidayah; Andry Akhiruyanto; Dewangga Yudhistira; Haris Kurnianto (OVS LLC, 2023)
Study purpose. The purpose of this research is to determine the effect of LTAD-based programming on the physical abilities and fundamental skills of basketball players aged 11-12 years. Materials and methods. The research method used was an experimental one-group pretest-posttest design. The study participants included 50 basketball players, 25 males and 25 females, weighing ±50-70 kg and standing 159-172 cm tall.The instruments used consisted of a multistage fitness test, 30-meter sprint, Illinois run, layup, shooting under the ring, and free throw. Data was gathered by observation and testing. The data was analyzed descriptively using Wilcoxon and Mann-Whitney tests, which were aided by SPSS version 23. Results. The results of the male and female groups' pretest-posttest showed that the Asymp.sig (2-tailed) values for the aspects of endurance, speed, agility, layup, shooting under the ring, and free throw were 0.000<0.05. The results of the posttest comparison between males and females revealed that the Asymp.sig (2-tailed) value for the aspects of endurance, agility, speed, layup, and free throw was 0.264-0.938>0.05, only for shooting under the ring the Asymp.sig (2-tailed) value was 0.008 <0.05. Conclusions. The male and female groups' posttest results were better than the pretest results before LTAD-based programming. The majority of the posttest comparisons between males and females revealed no significant differences. This suggests that both the male and female groups improved after receiving LTAD-based programming.